Possibilities of predicting the HER2 / neu status in a primary tumor in breast cancer patients using 99mTc-DARPinG3 - O. D. Bragina; L. A. Tashireva; V. I. Chernov; S. M. Deyev; V. M. Tolmachev (Бюллетень сибирской медицины, 2023)
Aim. To determine informative prognostic criteria for assessing the HER2 / neu status in primary breast cancer using 99mTc-DARPinG3.Materials and methods. The study included 10 patients with breast cancer (T1-4N0-2M0) before systemic therapy, who underwent a radionuclide study using 99mTc-DARPinG3 at a dose of 3,000 μg. Five patients were characterized by HER2 / neu overexpression in primary breast cancer, whereas 5 patients were HER2-negative. For all patients, morphological and immunohistochemical studies and fluorescence in situ hybridization (FISH) of the primary tumor nodule were carried out. Single-photon emission computed tomography (SPECT) of the chest was performed for all patients 4 hours after the injection of 99mTc-DARPinG3.Results. The total activity of 99mTc-DARPinG3 was 522.4 ± 341.8 MBq. The comparative analysis showed that higher uptake of the labeled protein in HER2-positive breast cancer was significant (p = 0.0159, Mann – Whitney U test). The analysis of the ratios showed significant differences in the tumor-to-background ratios in patients with HER2-positive breast cancer (p < 0.0159, Mann – Whitney U test). Based on the logistic regression analysis, a mathematical model was developed to predict the status of HER2 / neu in primary breast cancer patients (specificity and sensitivity 100%; p = 0.0004) using 99mTc-DARPinG3 at a dose of 3,000 mcg 4 hours after the injection of the radiopharmaceutical.Conclusion. The results of the study allow to consider the tumor-to-background ratio 4 hours after the injection of 99mTc-DARPinG3 as an additional prognostic parameter for determining the HER2 / neu status in primary breast cancer.